PENGARUH TEKNOLOGI INFORMASI DAN KEAHLIAN KOMPUTER TERHADAP SISTEM INFORMASI AKUNTANSI PADA RUMAH SAKIT SWASTA DI KOTA PEKANBARU - Yesi Irawati; Yusralaini '; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to empirically examine the effect of information technology and computer expertise on Accounting Information Systems (AIS). This study was conducted on 18 Private Hospital in the city of Pekanbaru. Existing questionnaires distributed 72 pieces. Analysis tools used in this study is multiple regression.Advances in information technology affect the development of Accounting Information Systems (AIS) in terms of data processing, internal control, and increase the amount and quality of information and financial reporting. Due to transform data into information needed knowledge and expertise in running the information system. Many ways you can do to get those skills, one of which is the training or education.Once tested, it turns the information technology and computer expertise had a strong influence on Accounting Information Systems (AIS) with an adjusted R2 of 71.8%, while 28.2% influenced by other factors.Based on the responses obtained from 64 respondents, the authors conclude that information technology and computer skills together - the same significant effect on Accounting Information Systems (AIS) .Uji partially, information technology and expertise also significantly influence the Accounting Information Systems (AIS).Keywords: information technology, computer skills, Accounting Information Systems (AIS)